Heterogeneous Preferences for Neighborhood Amenities: Evidence from GPS Data - Cook, Cody (The Review of Economics and Statistics, 2025)
How do preferences for neighborhood amenities vary by income? Using data on over 100 million visits to 1.4 million establishments, I estimate a discrete choice model of demand for restaurants, shops, personal services, and entertainment places. While preferences for specific establishments often vary by income, preferences for neighborhoods' overall amenity access are highly aligned. The primary determinant is density: dense urban areas have sufficient variety to offer broad appeal. For incumbents of gentrifying neighborhoods, tailoring amenities to higher-income entrants has only modest welfare effects relative to the effects of potential displacement to cheaper neighborhoods with worse access to amenities.